Students’ Daily Attendance Management System. - Komurembe, Phionah; Rukundo, Emmanuel (Kabale University, 2024)
This final year project focused on developing a Daily Student Attendance Management System to replace traditional attendance tracking methods with a more streamlined, precise, and dependable solution. Attendance is a vital metric in educational institutions, essential for record-keeping and evaluating student performance. However, manual methods often lead to data inaccuracies, inefficiencies, and added administrative challenges. This project introduced a web-based system that automates attendance recording and report generation to address these issues, enhancing operational efficiency and usability. The system provides an intuitive interface for teachers and administrators, enabling real-time tracking and management of student attendance data. By minimizing human errors and ensuring data accuracy, it supports better decision-making in budgeting and resource allocation. The system was developed using web-based programming languages, including HTML, CSS, and PHP, with MySQL employed for database management. Rigorous testing ensured optimal performance and functionality across various modules, such as student and staff management. Implementing this system is anticipated to enhance administrative processes, reduce workloads, and deliver more accurate data for informed decision-making. Future enhancements may include integrating advanced features such as biometric attendance tracking and expanding the system's scope to accommodate additional departments within the institution.